Profiles of VGF Peptides in the Rat Brain and Their Modulations after Phencyclidine Treatment - Noli, Barbara; Sanna, Fabrizio; Brancia, Carla; D’Amato, Filomena; Manconi, Barbara; Vincenzoni, Federica; Messana, Irene; Melis, Maria R.; Argiolas, Antonio; Ferri, Gian-Luca; Cocco, Cristina (Frontiers in Cellular Neuroscience, 2017)
From the VGF precursor protein originate several low molecular weight peptides, whose distribution in the brain and blood circulation is not entirely known. Among the VGF peptides, those containing the N-terminus portion were altered in the cerebro-spinal fluid (CSF) and hypothalamus of schizophrenia patients. “Hence, we aimed to better investigate the involvement of the VGF peptides in schizophrenia by studying their localization in the brain regions relevant for the disease, and revealing their possible modulations in response to certain neuronal alterations occurring in schizophrenia”. We produced antibodies against different VGF peptides encompassing the N-terminus, but also C-terminus-, TLQP-, GGGE- peptide sequences, and the so named NERP-3 and -4. These antibodies were used to carry out specific ELISA and immunolocalization studies while mass spectrometry (MS) analysis was also performed to recognize the intact brain VGF fragments. We used a schizophrenia rat model, in which alterations in the prepulse inhibition (PPI) of the acoustic startle response occurred after PCP treatment. In normal rats, all the VGF peptides studied were distributed in the brain areas examined including hypothalamus, prefrontal cortex, hippocampus, accumbens and amygdaloid nuclei and also in the plasma. By liquid chromatography-high resolution mass, we identified different intact VGF peptide fragments, including those encompassing the N-terminus and the NERPs. PCP treatment caused behavioral changes that closely mimic schizophrenia, estimated by us as a disruption of PPI of the acoustic startle response. The PCP treatment also induced selective changes in the VGF peptide levels within certain brain areas. Indeed, an increase in VGF C-terminus and TLQP peptides was revealed in the prefrontal cortex (p < 0.01) where they were localized within parvoalbumin and tyrosine hydroxylase (TH) containing neurons, respectively. Conversely, in the nucleus accumbens, PCP treatment produced a down-regulation in the levels of VGF C-terminus-, N-terminus- and GGGE- peptides (p < 0.01), expressed in GABAergic- (C-terminus/GGGE) and somatostatin- (N-terminus) neurons. These results confirm that VGF peptides are widely distributed in the brain and modulated in specific areas involved in schizophrenia.